APPLYING AI TO MARKET VOLATILITY ANALYSIS - Rasulov Abdukodir Komiljon ugli (Modern American Journals, 2025)
The global economy is currently changing rapidly. Market volatility is a phenomenon caused by prices, supply and demand, investor confidence, and other factors. Traditional statistical methods are often slow and inaccurate in predicting such changes. Therefore, the use of artificial intelligence (AI) technologies is becoming increasingly important in analyzing market volatility with depth and accuracy. This article analyzes the processes of identifying, modeling, and predicting market volatility using artificial intelligence.
Keywords: Market volatility, artificial intelligence, analysis, investors, global economy